A software tool for high-throughput real-time measurement of intensity-based ratio-metric FRET - Ramuz,M; Hasan,A; Gruscheski,L; Diakonov,I; Pavlaki,N; Nikolaev,VO; Harding,S; Dunsby,C; Gorelik,J (Cells, 2019)
Förster resonance energy transfer (FRET) is increasingly used for non-invasive measurement of fluorescently tagged molecules in live cells. In this study, we have developed a freely available software tool MultiFRET, which, together with the use of a motorised microscope stage, allows multiple single cells to be studied in one experiment. MultiFRET is a Java plugin for Micro-Manager software, which provides real-time calculations of ratio-metric signals during acquisition and can simultaneously record from multiple cells in the same experiment. It can also make other custom-determined live calculations that can be easily exported to Excel at the end of the experiment. It is flexible and can work with multiple spectral acquisition channels. We validated this software by comparing the output of MultiFRET to that of a previously established and well-documented method for live ratio-metric FRET experiments and found no significant difference between the data produced with the use of the new MultiFRET and other methods. In this validation, we used several cAMP FRET sensors and cell models: i) isolated adult cardiomyocytes from transgenic mice expressing the cytosolic epac1-camps and targeted pmEpac1 and Epac1-PLN sensors, ii) isolated neonatal mouse cardiomyocytes transfected with the AKAP79-CUTie sensor, and iii) human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) transfected with the Epac-SH74 sensor. The MultiFRET plugin is an open source freely available package that can be used in a wide area of live cell imaging when live ratio-metric calculations are required.